PROBLEMS AND CHALLENGES IN 21ST CENTURY BIOLOGY LEARNING: A QUALITATIVE STUDY - Amrianto, Amrianto; Rohman, Fatchur; Dharmawan, Agus; Sari, Murni Sapta (Research and Development Journal of Education, 2025)
Biology learning involves real-world problems including biodiversity, plants, and animals, as well as those important to students' daily lives. Biology learning in the 21st century is meant to give students active, relevant, and contextual learning, and it is directly tied to digitalization. This study aims to investigate the problems and challenges in teaching biology in public high schools in Kerinci Regency, Indonesia, in light of the needs of the 21st century. This is a survey study using qualitative data. A questionnaire was used as an instrument. Simple random sampling is used in the sampling procedure. The study included 166 students and 14 high school biology teachers who participated in this study from across Kerinci Regency. The Miles and Huberman approach is used in the data analysis technique, aided by the Atlas. ti 22 program. According to the findings, high school biology students and teachers in Kerinci Regency face several problems related to the biology study, including 1) latin language (biological terms); 2) laboratory (practicum); 3) material references (package books); and 4) learning that is considered uninteresting. The main challenges by biology teachers in the 21st century is adopting student-centered, active, meaningful, collaborative, and interesting learning. Technology is always evolving in the 21st century, biology teachers need to become more technologically and digitally literate.